Bioconcentration of Heavy Metals in Milkfish Reared in Stick-Net Pens System: Implications for Open Water Environmental Contamination and Food Safety - Martuti, Nana Kariada Tri; Falisah, Dwi Fiska; Sidiq, Wahid Akhsin Budi Nur; Melati, Inaya Sari; Mutiatari, Dhita Pracisca; Nayam, Nasir (Universitas Negeri Semarang, 2024)
The coast of Tanjung Mas, Semarang City, is an industrial area used by the community to cultivate milkfish using stick-net pens. Furthermore, heavy metal contamination such as Cr, Cd, Cu, and Pb potentially disrupts milkfish meat's growth, quality, and safety. This study aims to determine heavy metals concentration in the waters and milkfish meat in stick-net pens cultivation in Tanjung Mas, Semarang City. The study was conducted using exploration, with five observation sites representing household waste disposal flow, industrial discharge, open sea, and intermediate areas. The observation sites were selected based on the milkfish cultivation activity. The sample and data, including water, milkfish, and environmental factors (temperature, pH, salinity, water current, and dissolved oxygen), were collected three times every two weeks. The heavy metals were detected using Atomic Absorption Spectrometry (AAS). The highest heavy metal concentration is Cr, which ranges from 1.70 ± 0.32 ppm to 2.36 ± 0.63 ppm in milkfish and 2.77 ± 0.65 ppm to 3.05 ± 0.58 ppm in the environment. The heavy metals contamination in Semarang City’s water areas is still relatively low and has no impact on milkfish growth. Industrial waste, mainly heavy metals, potentially threatens the stick-net pens cultivation model developed by the community in Semarang City. This study can be used as an input for mitigation and adaptive action in anticipating future environmental changes and maintaining their business sustainability.